Thermal Neutron Flux Measurements at Room Treatment LINAC iX 15 MV - Risalatul Latifah; Johan A E Noor; Bunawas Bunawas (Natural B, Journal of Health and Environmental Sciences, 2013)
Linac is operated at above 10 MV will generate secondary radiation in the form of neutron emission from the reaction of the high photon energy linac striking the material components of linac such us targets, collimators and filters. Secondary radiation will increase the probability of the secondary cancer risk in patients due to increasing the dose of radiation received. This study evaluated the thermal neutron flux at the indoor spatial operated 15 MV linac using foil activation method. A total of 14 Indium-115 foil placed in the treatment room were exposed to 15 MV linac plane for 1 minute. Results showed the highest flux are around isocenter . With the flux value of additional dose due to the neutron flux at Sv/menit. FLux decreases as distance function. Related to radiation protection efforts for radiation workers, the contribution coming from the neutron dose necessary acted upon by adding shielding on the door.